Processes for Trauma Care at Six Level I Trauma Centers During the COVID-19 Pandemic. Issue 1 (January 2021) - Harwood, Laura; Jarvis, Stephanie; Salottolo, Kristin; Redmond, Diane; Berg, Gina M.; Erickson, Wendy; Spruell, Dana; Deas, Shenequa; Sharpe, Paul; Atnip, Amy; Cornutt, David; Mains, Charles; et al.
ABSTRACT: Introduction: As the COVID-19 pandemic spread, patient care guidelines were published and elective surgeries postponed. However, trauma admissions are not scheduled and cannot be postponed. There is a paucity of information available on continuing trauma care during the pandemic. The study purpose was to describe multicenter trauma care process changes made during the COVID-19 pandemic. Methods: This descriptive survey summarized the response to the COVID-19 pandemic at six Level I trauma centers. The survey was completed in 05/2020. Questions were asked about personal protective equipment, ventilators, intensive care unit (ICU) beds, and negative pressure rooms. Data were summarized as proportions. Results: The survey took an average of 5 days. Sixty-seven percent reused N-95 respirators; 50% sanitized them with 25% using ultraviolet light. One hospital (17%) had regional resources impacted. Thirty-three percent created ventilator allocation protocols. Most hospitals (83%) designated more beds to the ICU; 50% of hospitals designated an ICU for COVID-19 patients. COVID-19 patients were isolated in negative pressure rooms at all hospitals. Conclusions: In response to the COVID-19 pandemic, Level I trauma centers created processes to provide optimal trauma patient care and still protect providers. Other centers can use the processes described to continue care of trauma patients during the COVID-19 pandemic.